Analisis Pengaruh Company Size, Return on Assets, Financial Leverage, dan Operating Leverage terhadap Income Smoothing Practices pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Auditya Williyarto Pradana; Sunaryo Sunaryo (Binus Business Review, 2012)
The primary objectives of this research is to learn the amounts of industrial company using income smoothing practices and effecting among company size, return on assets, financial leverage, and operating leverage with income smoothing practices neither simultaneous nor partial. Data secondary collected by industrial companies listed at Indonesian Stock Exchage and the journal preceding research persons. The sesults of this research describe that there are 11 from 31 samples of industrial company using income smoothing practices. Company size, Return on assets, and financial leverage have not any an effecting significant to income smoothing practices, and Operating leverage have an effecting significant to income smoothing practices, but Company size, Return on assets, Financial leverage, and Operating Leverage have the simultaneous effecting significants to income smoothing practices. The topic of this research can be continued using a certain industrial groups or added many new independence variables, because if compared to proceeding research persons who mention the same and differences of its.